The Role of Prophylactic Cervical Lymph Node Dissection with Total Thyroidectomy in Prevention Recurrence of Papillary Thyroid Carcinoma - Kadhim, Salah Hadi; Mahmood, Karrar Ibrahim; Habash, Mohammed Mohammud (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: It is assess benefit prophylactic selective unilateral cervical lymph node (LN) dissection with total thyroidectomy for patients who have papillary thyroid carcinoma (PTC) and negative cervical lymph nodes metastasis and determination recommended risk factors for such surgery. METHODS: This was a prospective study, 60 patients with PTC investigated by Fine needle aspiration, ultrasonography to support diagnosis patients with PTC, and negative lymph node metastasis. Nineteen patients are excluded from the entire 60 patients; remaining 41 patients are submitted to a total thyroidectomy and prophylactic selective one side ipsilateral lateral and central lymph nodes dissection (level II, III, IV, and V). Then, follow-up 2 years for all patients, postoperatively, for detection PTC recurrence. RESULTS: The result shows that from the total 41 patients, two groups are positive and negative lymph nodes metastasis 24.4% (10) and 75.6% (31), respectively, positive lymph nodes metastasis is presented more in male 7 (70%) with significant difference (p = 0.03) and age groups <55 years old 6 (60%) with insignificant association (p = 0.413). Thyroid nodular size (>1 cm) and multiple nodules presented more in positive lymph nodes metastasis with significant difference in both. Multivariate binary logistic regression, sex, thyroid multinodularity, and thyroid nodule size were insignificant relationship of prediction of lymph nodes metastasis. CONCLUSION: Prophylactic cervical LN dissection with total thyroidectomy for patients with PTC and negative cervical lymph nodes metastasis has beneficial role in preventing recurrence of PTC. Risk factors such as male gender, thyroid multinodularity (multiple nodule), and their size (>1 cm) have role in increasing chance of occurrence of cervical LN metastasis.